2006
DOI: 10.1038/sj.mp.4001841
|View full text |Cite
|
Sign up to set email alerts
|

MPZL1/PZR, a novel candidate predisposing schizophrenia in Han Chinese

Abstract: The MPZL1/PZR gene has been mapped to 1q23.3, located in close proximity to a recognized schizophrenia susceptibility locus. Recently, the MPZL1/PZR gene has been found to be significantly upregulated in schizophrenia brain tissue and to play an important role in cell signaling, thus indicating that MPZL1/PZR could be a potential schizophrenia marker. To test this hypothesis, we selected three single nucleotide polymorphisms (SNPs) for genotyping in 523 Han Chinese trios. We found that two individual SNPs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The gene MPZL1 (MIM#604376), contacted by both KCTD13 and SH2B1, is associated with SCZ. 92 It is a downstream target of PTPN11 . 93 …”
Section: Methodsmentioning
confidence: 99%
“…The gene MPZL1 (MIM#604376), contacted by both KCTD13 and SH2B1, is associated with SCZ. 92 It is a downstream target of PTPN11 . 93 …”
Section: Methodsmentioning
confidence: 99%
“…Tkachev et al 16 found that MPZL1/PZR was significantly upregulated in schizophrenia patients compared with healthy controls (1.29-fold, P=0.0263). Common SNPs in MPZL1/PZR gene were recently reported to be associated with schizophrenia in 523 case-parent triad family of Han Chinese (P=0.0017) 17 .…”
mentioning
confidence: 99%
“…We previously reported that DNA methylation status in the CpG island of the SRY (sex determining region Y)‐box 10 ( SOX10 ) gene correlated with a downregulated expression of SOX10 and other oligodendrocyte‐related genes 8 . In addition, several oligodendrocyte‐related genes have been proposed to be susceptibility genes for schizophrenia, including myelin‐oligodendrocyte glycoprotein ( MOG ), 15 myelin‐associated glycoprotein ( MAG ), 16,17 proteolipid protein 1 ( PLP1 ), 18 gelsolin ( GSN ), 19 oligodendrocyte lineage transcription factor 2 ( OLIG2 ), 20 myelin protein zero‐like 1 ( MPZL1 ), 21 and 2′,3′‐cyclic nucleotide 3′‐phosphodiesterase ( CNP ) 22 . Although none of them have yet been replicated across different populations, 23,24 identifying the primary cause of the change would provide important insights into the pathophysiology of schizophrenia.…”
mentioning
confidence: 99%